Quantum Dot–Based Solar Cells: Advancements, Challenges, and Future Prospects (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Quantum dot–based solar cells have rapidly grown into one of the most promising candidates in next-generation photovoltaics, largely due to their quantum confinement–driven tunability, strong absorption coefficients, and compatibility with solution-processed fabrication. Their unique optical behaviour, particularly the ability to tailor bandgaps simply by adjusting nanocrystal size, offers a conceptual advantage over conventional bulk semiconductors. Over the past decade, improvements in surface passivation, ligand chemistry, nanocrystal synthesis, and device architecture have enabled efficiencies exceeding 18%, reflecting an impressive rise from early single-digit values (Ning et al., 2022). Yet, despite these encouraging advances, the field continues to face challenges related to long-term stability, environmental toxicity, and large-scale manufacturability. This paper traces the evolution of quantum dot solar cell research, highlighting key breakthroughs in material design, mechanistic understanding, and interfacial engineering, while also discussing the scientific and technological hurdles that must be confronted before widespread commercial adoption becomes feasible. The analysis suggests that continued collaboration between materials scientists, device engineers, chemists, and computational researchers will be crucial for realising the full potential of quantum dot photovoltaics in a sustainable global energy landscape.